ANALISA PENGENDALI HYBRID SLIDING MODE CONTROL DAN PID UNTUK MENGENDALIKAN CONCENTRATION PADA ISOTHERMAL CONTINUOUS STIRRED TANK REACTOR (CSTR) - Ahmad Faizal; Dian Mursyitah; Ewi Imaredah; Muhammad Ikhsyan (Jurusan Teknik Elektro, Universitas Bangka Belitung, 2018)
Systems in industry often occur in performance or desired performance. One of them isothermal CSTR system where the system has not been able to work according to the desired set point 1 g.mol / litter, to achieve the set point then used the controller Sliding Mode Control in Hybrid with PID in identification with FOPDT method to lower the value steady state error From the controller obtained results where the Sliding Mode Control Hybrid PID is able to not achieve set point value 1 g.mol / litter with ts = 3.0446 seconds.